THE INFLUENCE OF EDUCATIONAL ONLINE GAMES ON STUDENT LEARNING MOTIVATION - Nadia Wulandari; Moch. Bahak Udin By Arifin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
Online games use multimedia that is made as attractive as possible so that players get batik satisfaction and use internet access. So online games can have an impact on student learning motivation. This study aims to determine and analyze online games' influence on student learning motivation at SD Muhammadiyah 1 Waru, Sidoarjo Regency. The type of research used is quantitative. Data collection techniques use questionnaires and documentation of students. The results of research that has been conducted show 1) Online games affect learning motivation in students; 2) The application of a comprehensive technology learning process is one alternative strategy to deal with students who have online game addiction; 3) Based on the results of research on children, it can be seen that a) children spend 15% of the time playing the Internet for 30 minutes, then increase by 25% for 2 to 3 hours in one day; b) 60% of children play the Internet for 5 hours per day or more than 5 hours during school holidays. Based on the findings of a simple linear regression test, it was found that the r-count has a significance level of 5%, which is 0.703 > 0.444, and the r-count > the r-table. Thus, Ha believes that online games influence grade students' motivation to learn at SD Muhammadiyah 1 Waru Kabupateln Sidolarjol is acceptable. Hypothesis tests show a significant effect of educational online games on learning motivation in grade 3, 4, and 5 students of SD Muhammadiyah 1 Waru.